СУЧАСНІ ІНФОРМАЦІЙНІ ТЕХНОЛОГІЇ У ВИРІШЕННІ ЗАДАЧ ЕЛЕКТРОТЕХНІКИ ТА ПІДВИЩЕННЯ НАДІЙНОСТІ ЕЛЕКТРОТЕХНІЧНОГО ОБЛАДНАННЯ - Шидловська, Н.А.; Васецький, Ю.М.; Мислович, М.В.; Хімюк, І.В. (Інститут електродинаміки НАН України, Київ, 2023)
The mail scientific results are discussed which were obtained in the department of theoretical electrical engineering of the Institute of electrodynamics of Ukrainian National Academy of Sciences on the outcome of the implementation of scientific work ”Complex-2 ", which was performed during the 2000–2010 period. Researches were conducted in the main areas of department’s work: development of theory and creation of effective analytical methods of research of processes in nonlinear electric circuits; development of asymptotic methods of numerical-analytical computation of the electromagnetic systems; development of theory and methods of the practical use of the informative-measuring systems of statistical diagnostics of power electrical equipment; development of mathematical models and numerical research of the linked electromagnetic, mechanical and acoustic fields in the power electrical equipment. References 38, table 1, figures 6.